2009
DOI: 10.1093/nar/gkp342
|View full text |Cite
|
Sign up to set email alerts
|

Functional mapping of the interaction between TDP-43 and hnRNP A2 in vivo

Abstract: Nuclear factor TDP-43 has been reported to play multiple roles in transcription, pre-mRNA splicing, mRNA stability and mRNA transport. From a structural point of view, TDP-43 is a member of the hnRNP protein family whose structure includes two RRM domains flanked by the N-terminus and C-terminal regions. Like many members of this family, the C-terminal region can interact with cellular factors and thus serve to modulate its function. Previously, we have described that TDP-43 binds to several members of the hnR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
221
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(231 citation statements)
references
References 60 publications
10
221
0
Order By: Relevance
“…Although it has been demonstrated that TDP-43 itself is intrinsically aggregation-prone (57) and contains prion-like properties within its C terminus (58-60), we have found that motor neuron disease develops in the TDP-43 mutant-expressing mice without detectable TDP-43 aggregation. Furthermore, the TDP-43 C terminus has been proposed by others to play a role in association with other proteins in splicing of target genes (16)(17)(18)61), although the contribution of mutations in the C terminus to the disruption of TDP-43 splicing function was not well understood. Indeed, a study using a human cell-culture model expressing TDP-43 Q331K and TDP-43 M337V found that mutations in the TDP-43 C terminus do not alter the composition of complexes of known TDP-43-interacting hnRNPs, nor the splicing of a cystic fibrosis transmembrane conductance regulator-based splicing reporter (17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although it has been demonstrated that TDP-43 itself is intrinsically aggregation-prone (57) and contains prion-like properties within its C terminus (58-60), we have found that motor neuron disease develops in the TDP-43 mutant-expressing mice without detectable TDP-43 aggregation. Furthermore, the TDP-43 C terminus has been proposed by others to play a role in association with other proteins in splicing of target genes (16)(17)(18)61), although the contribution of mutations in the C terminus to the disruption of TDP-43 splicing function was not well understood. Indeed, a study using a human cell-culture model expressing TDP-43 Q331K and TDP-43 M337V found that mutations in the TDP-43 C terminus do not alter the composition of complexes of known TDP-43-interacting hnRNPs, nor the splicing of a cystic fibrosis transmembrane conductance regulator-based splicing reporter (17).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the TDP-43 C terminus has been proposed by others to play a role in association with other proteins in splicing of target genes (16)(17)(18)61), although the contribution of mutations in the C terminus to the disruption of TDP-43 splicing function was not well understood. Indeed, a study using a human cell-culture model expressing TDP-43 Q331K and TDP-43 M337V found that mutations in the TDP-43 C terminus do not alter the composition of complexes of known TDP-43-interacting hnRNPs, nor the splicing of a cystic fibrosis transmembrane conductance regulator-based splicing reporter (17). In contrast, using a true in vivo context in mice that develop progressive motor neuron disease, we have found widespread splicing alterations in the adult mammalian central nervous system in the presence of nuclear, mutant TDP-43.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is distinct from the insoluble protein aggregates, formation of which is inhibited by TG-repeat nucleotide binding in vitro [18]. We have also observed that TDP-25A, a C-terminal fragment of TDP-43 containing only the RRM2 domain that binds nucleic acids much more weakly than RRM1 [37], cannot associate with TDP-43 either by RNA or synthesized ssDNA (Fig. 1).…”
Section: Discussionmentioning
confidence: 71%
“…TDP-43 recognizes (UG) n repeat elements in target mRNAs by its RRM1 [128,129]. The glycine-rich domain mediates the interactions between TDP-43 and other proteins such as hnRNPs [130]. TDP-43 also contains a Q/N-rich prion-like element that mediates its interaction with polyQ aggregates.…”
Section: Rrm-rgg Families: Tdp-43 and Fusmentioning
confidence: 99%